The EarthCARE mission: science data processing chain overview - M. Eisinger; F. Marnas; K. Wallace; T. Kubota; N. Tomiyama; Y. Ohno; T. Tanaka; E. Tomita; T. Wehr; D. Bernaerts (Atmospheric Measurement Techniques, 2024)
The Earth Cloud Aerosol and Radiation Explorer (EarthCARE) is a satellite mission implemented by the European Space Agency (ESA) in cooperation with the Japan Aerospace Exploration Agency (JAXA) to measure vertical profiles of aerosols, clouds, and precipitation properties together with radiative fluxes and derived heating rates. The data will be used in particular to evaluate the representation of clouds, aerosols, precipitation, and associated radiative fluxes in weather forecasting and climate models.